The Bowker annual of library and book trade information - Council of National Library and Information Associations (U.S.).; Council of National Library Associations; R.R. Bowker Company (New York R.R. Bowker, 1955)
Annual
Editors: 1955/56- W.E. Wright and the editorial staff of R.R. Bowker company.
Sponsored by the Council of National Library Associations and the Library journal.
Title varies: 1955/56-58, American library annual.--1959, American library annual and book trade almanac.--library and book trade almanac.--1960-1961, American library & book trade annual.
Vols. for 1958- include indexes cumulative from 1955/56.
Keywords: Libraries -- United States -- Periodicals; Bibliography; Book industries and trade -- Periodicals; Book Industry -- United States -- Directories; Information science -- Periodicals; Libraries -- United States -- Directories; Library Associations -- Directories; Library science -- Periodicals